Lavender of Peace - คำมา, อานุภาพ (Rangsit Music Journal, 2018)
The composition Lavender of Peace aims to represent Thailand’s musical culture to international. The first performance of Lavender of Peace was performed at Rangsit University and the second was shown at Thailand International Jazz Conference 2017 at College of Music, Mahidol University (Salaya). The third was shown at Big Band Madness 2017 at Taipei, Taiwan. Which all performance was performed by Rangsit University Jazz Orchestra. Lavender of Peace is an original contemporary composition for jazz orchestra that combines jazz and Thai’s traditional music. The fundamental basis of music and unique Thai’s refrain are raw materials for the composition by using the pentatonic scales and double-headed drum. Sonata form is used for the pattern overall structure of this composition. Time signature 3/4 4/4 and 6/4 were used in the composition. The different of texture between Pentatonic and Natural Minor scales had been used as an idea to create a melody. The harmony is derived from the sound of the main melody, which determines the kind of the harmony. The composer emphasizes on, an orchestration, role of each instrument including each group of instruments within the jazz orchestra. Also the improvisation parts that have been play by bass, guitar and saxophone.